Pendidikan Progresif-Moderatif untuk Meningkatkan Soft Skills Siswa MIM SUKA-AKA sebagai Inovator Perubahan Pendidikan - Prayitno, Harun Joko; Ratih, Koesoemo; Utami, Ratnasari Diah; Siswanto, Heri; Purnomo, Eko; Al Sanaani, Ali Essam; Taha A, Ali Abdulraoof; Nugroho, Febriyanto Arif; Sofiyudin, Muh; Jufriansah, Adi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
The approach, strategy, innovation, and collaboration of educators are vital to improving student competency in the era of global communication. One of the challenges students face in Indonesia is mastering English and Arabic. Community Service at MIM, AKA Mojogedang, Karanganyar, aims to improve the vocabulary of both languages through direct practice guided by native speakers from Yemen. As a result, students' English skills increased from 55% to 80%, while Arabic skills increased from 60% to 86%. This increase is significant because the interactive and direct learning approach does not only focus on theory. Through the development of continuous approaches and collaboration, this learning forms students who are more holistically competent and ready to face the challenges of global communication. This progressive and moderate education can equip students with essential skills in modern computing.